2013
DOI: 10.3109/08923973.2012.759962
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic alcohol contaminants of illegally produced spirits inhibit phagocytosis by human granulocytes

Abstract: Due to their synergistic effects, it is possible that, in combination with ethanol, they may inhibit phagocytosis in a clinically meaningful way in episodic heavy drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…According to Mann-Whitney test, the concentration of higher alcohols in unrecorded alcohol is significantly lower than in commercial alcohol (p50.0001). This is exactly the opposite than the assumption of Pál et al 1 In light that the consumption of recorded alcohol is larger than the one of unrecorded alcohol in most parts of the world, we conclude that recorded alcohol may be the ''main source of human exposure'' (to higher alcohols in particular, and aliphatic alcohols in general) rather than unrecorded alcohol. In fact, increased susceptibility to infectious diseases such as tuberculosis and HIV has been epidemiologically demonstrated to be related to levels of pure alcohol with no specificity for certain beverages [13][14][15] .…”
mentioning
confidence: 45%
See 3 more Smart Citations
“…According to Mann-Whitney test, the concentration of higher alcohols in unrecorded alcohol is significantly lower than in commercial alcohol (p50.0001). This is exactly the opposite than the assumption of Pál et al 1 In light that the consumption of recorded alcohol is larger than the one of unrecorded alcohol in most parts of the world, we conclude that recorded alcohol may be the ''main source of human exposure'' (to higher alcohols in particular, and aliphatic alcohols in general) rather than unrecorded alcohol. In fact, increased susceptibility to infectious diseases such as tuberculosis and HIV has been epidemiologically demonstrated to be related to levels of pure alcohol with no specificity for certain beverages [13][14][15] .…”
mentioning
confidence: 45%
“…(2) The suggestion that unrecorded spirits are the main source of human exposure to these substances is incorrect. None of the references provided by Pál et al 1 demonstrate this point. On the contrary, our recent research about unrecorded alcohol has clearly invalidated this assumption 4-6 -and even alcohol industry-financed studies did not detect a substantial difference between unrecorded and commercial forms of alcohol with respect to higher alcohol concentration 7 .…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Although the consequences of the ethanol consumption are sufficient to cause concern for public health, less attention has been paid to the possible immunotoxic effects of the higher alcohols found in alcoholic beverages. We have previously shown that AAs can inhibit superoxide-anion production and phagocytosis by human granulocytes 34,35 . Still, it is important to know whether these alcohols can also decrease phagocytic activity of monocytes, as this could exacerbate the already-impaired anti-microbial defences in heavy drinkers.…”
Section: Introductionmentioning
confidence: 99%